Performance e gênero: uma análise discursiva sobre feminilidade no TikTok - Pachioni, Isabelle Batista (Universidade Federal de São Carlos, 2025)
This study is situated at the intersection of the theoretical-methodological field of Discourse Analysis, based on the assumptions of Michel Pêcheux and Eni Orlandi, Digital Discourse Analysis (Dias, 2018; Paveau, 2021), and Gender Performativity Theory, formulated by Judith Butler (2003). It seeks to analyze the discursivity surrounding performances of gender and femininity in the digital sphere. The object of investigation consists of content circulated under the hashtags #imjustagirl, #cleangirl, #cleangirlaesthetic, #housewife, and #tradwife on the TikTok platform. This social network was chosen because it is understood as a privileged space for the circulation and reconfiguration of discourses on femininity and gender identity, resignified through aesthetic performances, which directly aligns with the research problem. The main objective is to understand the developments and meaning effects produced by discursive formulations about women as a gender category and feminine behaviors within the digital environment. To this end, the study mobilizes theoretical-analytical concepts from Discourse Analysis, such as conditions of production, discursive formations, subject-position, imaginary formations, and ideology, articulating them with the notions of gender, performance, and performativity, which are fundamental for constructing and deepening the object of study. The methodology adopted is Discourse Analysis, considering its theoretical and analytical apparatus that combines procedures of description and interpretation of the corpus. This work aims to contribute to the understanding of the relations between performance, performativity, and female gender identity, observing how they are constituted and manifested in the digital sphere.
Performance and gender: a discursive analysis of femIninity in TikTok
Keywords: Performatividade de gênero; Feminilidade; Análise de discurso; Digitalidade; TikTok; Gender performativity; Femininity; Discourse analysis; Digitality; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA; 5. Igualdade de Gênero; 4. Educação de Qualidade